An Analysis of Moral Value Potrayed in Paulo Coelho’s The Spy and Eka Kurniawan’s Cantik itu Luka: A Comparative Literature Analysis (LingPoet: Journal of Linguistics and Literary Research, 2022)
This  study  discusses  a  comparative  literary  study  of  two  literary  works  with different  nations  and  languages,  but  with  similar  motif,  which  is  Moral Values. This study uses  the  concept  of  Moral  Values  which  provides the  concept  of  values  that  have  a  Commitment  to  something  greater  than oneself, Self-respect  but  with  humility,  self-discipline,  and  acceptance  of personal responsibility, Respect and caring for others, Caring for other living things and the environment. This study employed a qualitative descriptive method, that  uses  the  data  sources the  two  novels  The  Spy  by  Paulo  Coelho  and Cantik itu Luka by Eka Kurniawan and the data is obtained from novel quotes of  the  data  in  the  form  of  words  and  sentences. Then, the results The novel The Spy fulfills these four moral values. Meanwhile, the  novel  Cantik  itu  Luka  only  fulfills  three  of  the  four  moral  values.